Curriculum Innovation and Pedagogical Transformation: Assessing BMASS and CMASS Effect on Pre-Service Teachers in Teacher Education at the University of Delta (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study investigates the effect of two curriculum innovation models—the Blended Modularized Active Support System (BMASS) and the Collaborative Modularized Active Support System (CMASS)—on the academic performance and pedagogical skills of pre-service teachers at the University of Delta, Agbor, Nigeria. Employing a quasi-experimental design with a pre-test, post-test, non-equivalent control group, 90 pre-service teachers were assigned to three groups: BMASS, CMASS, and a control group taught using traditional methods. Data were collected using an Academic Performance Test (APT) and a Pedagogical Competency Rating Scale (PCRS). Results were analyzed using ANCOVA. Findings revealed that students in the BMASS group significantly outperformed their peers in academic tests, while the CMASS group demonstrated superior development in pedagogical competencies. The control group showed the least improvement in both areas. These results underscore the value of learner-centered, modular, and technology-integrated instructional models in promoting meaningful learning and teaching proficiency in teacher education. The study concludes that both BMASS and CMASS are effective alternatives to traditional instruction and recommends their integration into teacher training curricula. The findings also highlight the need for policy reform, professional development for teacher educators, and investment in digital learning infrastructure. This study contributes to the discourse on curriculum transformation in higher education and offers practical strategies for improving teacher education in Nigeria and similar developing contexts.